Does Abnormal Preoperative Coagulation Status Lead to More Perioperative Blood Loss in Spinal Deformity Correction Surgery? - Li, Zheng; Yu, Bin; Zhang, Jianguo; Shen, Jianxiong; Wang, Yipeng; Qiu, Guixing; Cheng, Xinqi (Frontiers in Surgery, 2022)
To analyze the potential association between preoperative coagulation status and perioperative blood loss in spinal deformity correction surgery. The preoperative coagulation status and estimated blood loss (EBL) during operation, postoperative wound drainage, allogeneic transfusion during and after operation were recorded and analyzed. Among the 164 patients, 26 had a longer prothrombin time(PT) time, 13 had a lower fibrinogen level, 55 had a longer activated partial thromboplastin time (APTT), 2 had a longer thrombin time (TT) time and the platelet count (PLT) were all normal or higher than normal level. The mean EBL per surgical level was 77.8ml (range, 22 to 267ml) and the mean drainage per surgical level was 52.7ml (range, 7 to 168ml). Fifty-five patients and twelve patients underwent allogeneic transfusion during and after operation, respectively. The differences of EBL per surgical level, mean drainage per surgical level, the occurrences of allogeneic transfusion during and after operation between the patients with longer PT time, lower fibrinogen level, longer APTT or longer TT time and the normal controls were none significant(all P>0.05). Spearman correlation analysis showed that there was no correlation between PT, fibrinogen, APTT, TT time or PLT with EBL per surgical level, mean drainage per surgical level, or allogeneic transfusion during and after operation (all p>0.05). The abnormal preoperative coagulation status but not hemophilia does not lead to more perioperative blood loss or higher rate of perioperative allogeneic transfusion in spinal deformity correction surgery.